Can personality traits explain glass ceilings? - Matthias Collischon (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper investigates whether personality traits can explain glass ceilings (increasing gender wage gaps across the wage distribution). Using longitudinal survey data from Germany, the UK, and Australia, I combine unconditional quantile regressions with wage gap decompositions to identify the effect of personality traits on wage gaps. The results suggest that the impact of personality traits on wage gaps increases across the wage distribution in all countries. Personality traits explain up to 14.5% of the overall gender wage gap. However, controlling for personality traits does not lead to a significant reduction of unexplained wage gaps in most cases.
Keywords: C21; J16; J31; 330; non-cognitive skills; personality traits; unconditional quantile regression; gender wage gap; glass ceiling